The Effectiveness of Guided Inquiry Learning with JAS Approach on the Learning Result of Environmental Pollution Material - Nurmilla, Mauliya Fatiya; HB, F Putut Martin; Priyono, Bambang (Journal of Biology Education, 2018)
This research aims at finding out the effectiveness of guided-inquiry learning model with Natural Environmment Exploration (JAS) approach on students’ learning result of environmental pollution material. This recent study was conducted in MAN 1 Pati in the odd semester in academic year 2017/2018. The research design applied is non-equivalent control group design. The population for this research is the whole students in X MIA MAN 1 Pati which is divided into 5 classes, while the sample taken for this research was X MIA 1 and X MIA 4 selected by using purposive sampling technique. The result of this study showed that 86.96% of students in experimental class achieved score > 75 and there was a difference of mean in the posttest for experimental class and control class i.e conseutively 85 and 75.19. The result of t-test showed tcount 0.000<0.05 which means there is a signifficant difference between control and experimental class. It also achieved N-Gain > 0.3 with the mean by 0.54. For the class control, 65.38% of students accomplished > 75 and N-Gain 0.14. Based on the research result, it can be inferred that guided-inquiry learning with JAS approach is effective to improve students’ learning result for the subject material of environmental pollution.